Inovação tecnológica e a competitividade na orizicultura no município de São Mateus do Maranhão - MA - Garcia, Uelson Serra (2019)
Rice is a relevant crop for the country, both in the trade balance and in the diet of the consumer and stands out among the most produced and consumed foods in the world. Brazil is one of the largest producers in the world. Five Brazilian states stand out in production, Rio Grande do Sul, Santa Catarina, Tocantins, Mato Grosso and Maranhão, but there are large differences in productivity between them, which demonstrates the asymmetry in production, mainly due to the different technologies used by producers, especially in Maranhão, where there are the lowest indices in terms of productivity. However, it is considered a state with great potential for Brazilian production, with some municipalities having competitive advantages, especially edaphic conditions. However, factors such as the qualification of labor, land regularization, availability of credit, technical assistance, among others, have reduced the advantages that the state possesses, and even so, the municipality of São Mateus do Maranhão stands out, currently, with a significant increase in production, reaching one of the highest in the state, which could be even greater if there were more investments in innovation and technologies. For this reason, this work seeks to study technological innovation and competitiveness in rice production in this municipality, with the hypothesis that the low capacity to carry out innovations in the rice producing properties in São Mateus do Maranhão is linked to the low technological increase, which decreases the competitiveness of the rice production chain. And, through the literature, it is verified that research on innovations in the rice production chain are more restricted to the industrial sector, given the lack of work on innovation in the realm of properties. In order to verify the productive structure and the innovative environment that may be interfering with the development of rice cultivation, we sought to know the socioeconomic and technological profile of the producers, besides performing factor analysis and groupings to verify the factors that most influence the production, and define the clusters that make up the domain arrangement in local production. As a characteristic, rice production in São Mateus do Maranhão presents two systems of cultivation, irrigated and favored dry, with small, medium and large producers. The factorial analysis determined four factors that determine the productive structure, such as: Work, Process and Productive Establishment (TP & E), Production Technology, Commercialization and Corporate Type (TC & TS), Fertilization Management and Informatization and Outsourcing, that is, these factors are the main indicators that determine the process of technological innovation in the rice production of the municipality of São Mateus do Maranhão. The analysis of clusters allowed to define the different groups of producers, forming three clusters, Low technological intensity, Medium technological intensity, and Low technological intensity and high in Nutrient management.